Avian fauna of Aundha dam in Aundha Nagnath dist- Hingoli - Katore DP (International Journal of Life Sciences, 2017)
The Avian fauna of Aundha dam was studies fort four months from November 2016 to Feb 2016 which is 09 km away from pimpaldari to avin fauna total 50 bird’s species are detected our of which 25 were resident 20 were winter migrant, 08 were resident migrant, out of which 17 were omnivorous resident 15 were carnivorous, 10 were insectivores 5 were herbivorous and 2 were granivorous.